Akkadian magic literature: old Babylonian and old Assyrian incantations : corpus - context - praxis - Ṿaserman, Natan (Leipziger altorientalistische Studien, 2022)
Cover -- Title Pages -- Table of Contents -- List of Tables -- Preface and Acknowledgements -- Abbreviations -- Conventions -- Concordances -- I. Akkadian Incantations of the Early Second Millennium:An Overview -- 1.1 Definition of the Corpus -- 1.2 Thematic Division of the Corpus -- 1.3 Geographical Setting and Archaeological Context -- 1.3.1 Southern Mesopotamia -- 1.3.2 Central Mesopotamia -- 1.3.3 The Diyala Region -- 1.3.4 Upper Mesopotamia -- 1.3.5 Periphery of Mesopotamia -- 1.4 Physical Properties of Tablets Containing Incantations -- 1.4.1 Classification of Tablets -- 1.4.2 Format of Tablets -- 1.4.3 Use of Tablets -- 1.4.4 Drawings on Tablets -- 1.4.5 Paratextual Comments -- 1.5 The Praxis -- 1.5.1 Ex opere operantis: The Magic Practitioners -- 1.5.2 The Clients -- 1.5.3 Location of Magic Praxis -- 1.5.4 Geographical Horizon in Magic Texts -- 1.5.5 Time of Magic Praxis -- 1.5.6 Materia Magica -- 1.5.7 Deities -- 1.6 Ex opere operato: Magic Strategies -- 1.6.1 Direct Confrontation -- 1.6.2 Indirect Approach -- 1.6.3 Offering a Way Out -- 1.6.4 Ignoring Evil -- 1.7 Literary Devices -- 1.7.1 Sound-Based Devices -- 1.7.2 Syntagmatic Devices -- 1.7.3 Semantic Devices -- 1.7.4 Thematic Devices -- II. The Texts -- 2.1 Specific Diseases and Medical Problems -- 2.1.1 Bile -- 2.1.2 Childbirth -- 2.1.3 Childhood Disease -- 2.1.4 Gastrointestinal Problems -- 2.1.5 Jaundice -- 2.1.6 Maškadu -- 2.1.7 Orthopaedic Problems -- 2.1.8 Pox -- 2.1.9 Stye -- 2.1.10 Tooth -- 2.1.11 Various Diseases -- 2.2 Animals -- 2.2.1 Dogs -- 2.2.2 Fish -- 2.2.3 Flies and Bees -- 2.2.4 Goats -- 2.2.5 Pests -- 2.2.6 Scorpions -- 2.2.7 Snakes and Reptiles -- 2.2.8 Worms and Leeches -- 2.3 Humans -- 2.3.1 Anger -- 2.3.2 Baby (Quieting Cry) -- 2.3.3 Empowerment -- 2.3.4 Love and Sexual Attraction -- 2.3.5 Trial -- 2.3.6 Witchcraft -- 2.4 Supernatural Entities.